Analysis Of The Implementation Of The Internal Control System For Credit Disbursement At Ksp Kopdit Abdi Manggarai Timur - Ignasius Irwandi Aman; Lustry Rahayu; Junita Cestilia Nenabu (Entrepreneurship Faculty, Universitas Garut, 2026)
This study aims to examine credit distribution at KSP KOPDIT Abdi East Manggarai, the obstacles or challenges faced by the cooperative, and how internal control strategies can ensure effective credit distribution. The approach used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of the internal control system for credit distribution at KSP KOPDIT Abdi has been carried out quite effectively based on the Treadway Commission's Committee on Supporting Organizations (COSO) framework, which includes the control environment, risk assessment, control activities, information and communication, and monitoring.